2020
DOI: 10.3389/fpls.2020.563721
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and Purification of Gracilariopsis chorda Carbonic Anhydrase (GcCAα3) in Nicotiana benthamiana, and Its Immobilization and Use in CO2 Hydration Reactions

Abstract: Carbonic anhydrase (CA; EC 4.2.2.1) is a Zn-binding metalloenzyme that catalyzes the reversible hydration of CO 2. Recently, CAs have gained a great deal of attention as biocatalysts for capturing CO 2 from industrial flue gases owing to their extremely fast reaction rates and simple reaction mechanism. However, their general application for this purpose requires improvements to stability at high temperature and under in vitro conditions, and reductions in production and scale-up costs. In the present study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Next, we transformed the construct MSC-GtCel12A alone or together with BiP-bdSENP1-HA into the N. benthamiana leaves using agroinfiltration ( Figures 1B,C ) (Islam et al, 2019 ; Razzak et al, 2020 ). At 3, 5, and 7 days post infiltration (dpi), we isolated total protein extracts from the transformed leaves and analyzed them by western blotting using an anti-CBM3 antibody.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Next, we transformed the construct MSC-GtCel12A alone or together with BiP-bdSENP1-HA into the N. benthamiana leaves using agroinfiltration ( Figures 1B,C ) (Islam et al, 2019 ; Razzak et al, 2020 ). At 3, 5, and 7 days post infiltration (dpi), we isolated total protein extracts from the transformed leaves and analyzed them by western blotting using an anti-CBM3 antibody.…”
Section: Resultsmentioning
confidence: 99%
“…However, this tight binding can be considered beneficial for not only the efficient capture and recovery of target proteins but also the repeated utilization of target proteins. Previous studies have indicated that industrial enzymes such as carbonic anhydrases from different origins exhibit not only efficient enzyme activity but also high endurability, thereby allowing multiple reuses of produced enzymes (Kumari et al, 2020 ; Razzak et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations